(untitled) (Clinics, 2011)
BACKGROUND: The respiratory pattern is often modified or even blocked during flexibility exercises, but little is known about the cardiovascular response to concomitant stretching and the Valsalva maneuver (VM) in healthy subjects. OBJECTIVES: This study evaluated the heart rate (HR), systolic blood pressure (SBP), and rate-pressure product (RPP) during and after large and small muscle group flexibility exercises performed simultaneously with the VM. METHODS: Asymptomatic volunteers (N = 22) with the following characteristics were recruited: age, 22 ± 3 years; weight, 73 ± 6 kg; height, 175 ± 5 cm; HR at rest, 66 ± 9 BPM; and SBP at rest, 113 ± 10 mmHg. They performed two exercises: four sets of passive static stretching for 30 s of the dorsi-flexion (DF) of the gastrocnemius and the hip flexion (HF) of the ischio-tibialis. The exercises were performed with (V+) or without (V-) the VM in a counterbalanced order. The SBP and HR were measured, and the RPP was calculated before the exercise session, at the end of each set, and during a 30-min post-exercise recovery period. RESULTS: The within-group comparisons showed that only the SBP and RPP increased throughout the sets (p